Synthesis of Polycyclic Frameworks through Iron-Catalyzed Intramolecular [5+2] Cycloaddition - Liu, Yongjiang; Zhang, Yanhui; Wang, Xiao; Fu, Shaomin; Liu, Bo (Synlett, 2018)
A concise and efficient approach to the core of the C18/C19 diterpenoid alkaloids and phomopsterone B is reported. Both syntheses share the same iron-catalyzed intramolecular [5+2] cycloaddition to assemble the tricyclo[6.3.1.01,6]]dodecane skeleton. The following approach to the 6/5/6/7 tetracyclic core scaffold of C18/C19 diterpenoid alkaloids features a regioselective Grignard addition/thermal Claisen rearrangement/RCM cyclization. Meanwhile the synthetic steps to access the spiro 6/5/6 tricyclic subunits of phomopsterone B were characterized as intramolecular aldol reaction, Wacker oxidation, and Criegee reaction.
Keywords: C18/C19-diterpenoid alkaloids; phomopsterone B; Iron-catalyzed; [5+2] cycloaddition